Social Evolution - Childe, V. Gordon, (Brill | Manohar Publishers & Distributors, 2024)
This last seminal work by V. Gordon Childe covers the evolution of the human race from the perspective of anthropological, historical, and archaeological methodologies. Social Evolution discusses the emergence of human societies in the prehistoric age. Interestingly, Childe also covers the emergence of barbarism and savagery, which was part of the prehistoric era, and barbaric cultures in Europe, Mesopotamia, Egypt, and the Mediterranean regions, which were the centres of civilization. Based on certain archaeological findings, the sociological discourse on human civilization is constructed in this book. Highly recommended for students and scholars interested in the anthropology, sociology, and history of the prehistoric era.